Long‐term outcome of patients with POEMS syndrome: An update of the Mayo Clinic experience. Issue 6 (13th April 2016) - Kourelis, Taxiarchis V.; Buadi, Francis K.; Kumar, Shaji K.; Gertz, Morie A.; Lacy, Martha Q.; Dingli, David; Go, Ronald S.; Kapoor, Prashant; Lust, John A.; Hayman, Suzanne R.; Hwa, Yi; Rajkumar, S. Vincent; et al.
Abstract : Over the past decade, a number of changes have occurred in the diagnostic evaluation, management, and long‐term follow‐up of patients with POEMS syndrome at our institution. This study included 291 patients with POEMS syndrome diagnosed at the Mayo Clinic between 1974 and 2014. Patients diagnosed after 2003 had more features of the syndrome identified at diagnosis and were more likely to receive an autologous transplant (49% versus 8%, P  < 0.0001) and to have achieved a hematologic complete response (CR) to treatment (41% vs 25%, P  < 0.0001). With 2273 person‐years of follow‐up, 10‐year overall survival (OS) was 62% (95% C.I., 56%, 67%). On multivariate analysis, the three factors associated with superior OS were younger age (RR 0.98 [0.96–1.00]), albumin greater‐than 3.2 g/dL (RR 0.5 [0.32–0.89]) and attainment of complete hematologic response (RR 0.4 [0.2, 0.9]). This study confirms the very good long‐term outcomes of patients with POEMS syndrome and identifies two new prognostic risk factors: albumin at diagnosis and attainment of complete hematologic response. Am. J. Hematol. 91:585–589, 2016. © 2016 Wiley Periodicals, Inc.